The Prevalence of Self-Reported Halitosis and Oral Hygiene Practices among Libyan Students and Office Workers - Eldarrat, A (CoAction Publishing, 2008)
AIMS: The aims of this study were to assess the prevalence of self-reported halitosis, oral hygiene practices and related diseases among Libyan students and employees. METHODS: Six hundred self-administered structured questionnaires were used to investigate self-perception of halitosis and oral hygiene practices among a group of Libyan volunteers. Chi square test was used to detect significant differences between frequencies and to test correlation between self-perception of halitosis and measures of oral hygiene. RESULTS: Forty three percent of the subjects were males and 57% were females. Forty four percent of the males and 54% of the females revealed self-perception malodour. Malodour was reported with the highest frequency (68%) during wake up time. Malodour was perceived by 31.7% of the females and 23.4% of the males during the hand-on-mouth test (p=0.04). Significantly more females (89.9%) than males (75.7%) practiced brushing (p<0.001). Fifty one percent of the males and 49.6% of females had dental caries. Smoking was significantly (p<0.001) more prevalent among males (17%) than among females (1%). Brushing was practiced by 85% of non-smokers and 68% of smokers (p=0.004). About 71% of the subjects who practiced brushing reported malodour during wake up time in comparison to subjects who did not practice brushing (p=0.041). CONCLUSIONS: The prevalence of self-perceived malodour among the Libyan volunteers in this study is within the range of other studies. There is a great demand to reduce the incidence of dental caries and periodontal diseases.